The K-16 education movement: common themes across K-12 and higher education systems to inform development and evaluation - Kearney, Christopher A.; Fensken, Michael; Dupont, Randolph (Frontiers in Education, 2024)
The K-16 education movement broadly includes efforts to streamline educational pathways across K-12 and higher academic and other systems to enhance adult and career readiness and address inequitable opportunities and resources faced by many vulnerable students. The movement remains largely aspirational, however, with little consensus and few tenets available to guide K-16 program development and evaluation. This article presents a preliminary scoping review of several major student themes that crosscut K-12 and higher education systems and that could inform K-16 education initiatives. These themes include student progression and completion; student engagement; student mental health; and student demographic and generational characteristics. Each theme is explored with respect to commonalities across K-12 and higher education systems. Examples include risk/protective factors, ecological levels, barriers, sophisticated data analysis, intervention, school climate, belongingness, student-teacher interactions, academic warning signs, tiered/stepped care models, and demographic and generational changes. A key underlying thesis throughout the article is movement toward a dimensional perspective that considers student development, support needs, learning strategies, and other domains along an educational spectrum rather than as distinct K-12 and higher education categories.